Perbandingan Onset, Durasi Dan Masa Pemulihan Dari Kombinasi Anestesi Acepromasin-Propofol-Ketamin Dan Midazolam-Propofol-Ketamin Pada Anjing Lokal - Dhiu, Dalmasia Trisna; Utami, Tri; Ndaong, Nemay A (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2024)
This study aims to determine and compare the onset, duration and recovery period between the use of a combination of Acepromazine-Propofol-Ketamine and a combination of Midazolam-Propofol-Ketamine as an anesthetic drug in local dogs. Dogs are grouped into two treatment groups consisting of 3 local male dogs. Before the anesthetic agent was injected, each group was given premedication atropine sulfate at a dose of 0.02 mg / kg BW SC and 10 minutes later an induction of anesthesia was given. In treatment group 1, acepromazine (0.2 mg / kg BB) IV was administered, propofol (4 mg / kg BB) IV, and ketamine (4 mg / kg BW) IV. Group II was given anesthesia midazolam (0.2 mg / kg BB) IV, propofol (4 mg / kg BW) IV, and ketamine (4 mg / kg BW) IV. Observation and measurement of the onset, duration and recovery period were carried out after the animal was induced with an anesthetic agent. The results of the study obtained the following data: KI group produced an average onset of 94 seconds, duration of 30 minutes and recovery period of 30.33 minutes. KII produces an onset of 45.33 seconds, duration of 17.66 minutes and recovery time of 16 minutes. Based on the results of the study it can be concluded that the combination of midazolam-propofol-ketamine has a faster onset, duration and recovery period compared to the combination of acepromasizine-propofol-ketamine in local male dog.